Current chemotherapy strategies for adults with IDH-wildtype glioblastoma - Bao, Jing; Sun, Rui; Pan, Zhenjiang; Wei, Shepeng (Frontiers in Oncology, 2024)
Introduction: Glioblastoma, despite advancements in molecular evolution, remains incurable and has low survival rates. Currently, two of the most commonly used chemotherapy regimens are temozolomide and CCNU. This review aims to provide a comprehensive analysis of the current status of chemotherapy strategies for GBM.We reviewed the published literature describing the chemotherapy regimen differences in system treatment of GBM reported temozolomide, but there are no better alternatives. Clinical trial participation is encouraged.